The needs of families accompanying injured patients into the emergency department in a tertiary hospital in Gauteng - Meghan L. Botes; Gayle Langley (AOSIS, 2016)
Background: Families are not prepared for traumatic injuries of loved ones. Emergency nurses have the important role of caring for patients and families in this time of crisis. Family needs in the critical care setting have been explored using the Critical Care Family Needs Inventory (CCFNI), however little is known about family needs in the emergency department. Objectives: This study sought to determine the needs of family members accompanying injured patients into the emergency department, and if these needs were met. Methods: A quantitative, descriptive, study was conducted in a level 1 trauma facility in Johannesburg, South Africa. The population included families of patients admitted to the emergency department, sampling 100 participants. The instrument, based on the CCFNI, was validated in a pilot study in Melbourne, Australia and re-evaluated using the Cronbach Alpha validity test to ensure internal consistency. Five themes were explored: 'meaning', 'proximity', 'communication', 'comfort' and 'support' and data were analysed using descriptive statistics. Responses to open-ended questions were analysed using content analysis. Permission from the Human Research Ethics Committee was granted and participants were ensured confidentiality and the option for counselling if required. Results: Themes ranked highly important were 'meaning' and 'communication'. Satisfaction was highest for 'meaning'. Low satisfaction levels for 'communication' were found. Issues regarding prolonged time spent in the emergency department and discrimination were raised. Conclusion: These findings have a negative impact on the family's satisfaction with care and it is recommended that the nurse's role in family care be further explored and emphasised. Keywords: Family needs, emergency department, emergency nurses